The ethnic project : transforming racial fiction into ethnic factions - Bashi Treitler, Vilna (Stanford studies in comparative race and ethnicity., 2013)
Race is a known fiction-there is no genetic marker that indicates someone's race-yet the social stigma of race endures. In the United States, ethnicity is often positioned as a counterweight to race, and we celebrate our various hyphenated-American identities. But Vilna Bashi Treitler argues that we do so at a high cost: ethnic thinking simply perpetuates an underlying racism. In The Ethnic Project, Bashi Treitler considers the ethnic history of the United States from the arrival of the English in North America through to the present day. Tracing the histories of immigrant a.